Fixed Point Theorems by Using Altering Distance Function in S-Metric Spaces - Kumar, Manoj; Devi, Sushma; Singh, Parul (Communications in Mathematics and Applications, 2022)
In the present paper, we prove some fixed point theorems by using the non-decreasing mapping \(κ :R^+→ R^+\) known as altering distance function or control function, in the context of \(S\)-metric space. Further, we explore the property \(P\) for these contractive mappings.